ARTAR-Artistic Augmented Reality. (2016) - Nithin, G.; Bhooshan, Reshmi S.
Abstract: Augmented reality is a technique which adds computer generated virtual objects into the real world scene. ARTAR proposes a method to enhance the experience of paintings or artistic works by adding an extra level of perception through the inclusion of sound, music, and animations. It contains two layers of perception, the physical appearance of the paintings perceived by naked eye and an augmented layer containing animations and sounds which can be perceived by a mobile device. When an artwork is scanned using a predesigned mobile application certain image reference portions get animated along with some music and sound. In this work, a reference area is found in the input video frame using SURF detector and BRISK descriptor and the virtual object is placed in the particular position. Experimental result shows that SURF-BRISK combination provides better result when compared with other detector descriptor combinations in case of ARTAR.